Laying Performance, Egg Quality Characteristics, and Egg Yolk Fatty Acids Profile in Layer Hens Housed with Free Access to Chicory- and/or White Clover-Vegetated or Non-Vegetated Areas - Canan Kop-Bozbay; Ahmet Akdag; Ayfer Bozkurt-Kiraz; Merve Gore; Orhan Kurt; Nuh Ocak (Animals, 2021)
This study investigated the laying performance, egg quality, and egg yolk fatty acids (FAs) and cholesterol content in layer hens housed with free access to chicory- and/or white clover-vegetated areas. During a 16-week study, 400 Lohmann Brown hens (32 weeks old) housed with free outdoor access were allocated randomly into four groups, each with four replicates of 25 hens. Control hens were fed a conventional diet with free access to a soil area (C), whereas other hens were fed on a conventional diet with free access to a chicory (CI)- or white clover (TR)-vegetated area or a CI and TR mixture (MIX)-vegetated area. The C hens consumed more concentrate feed (p = 0.018) than the TR and MIX hens, which had a higher herbage intake than the CI birds (p < 0.001). The C hens produced eggs with a thicker shell than those in the other treatment groups (p = 0.013). Compared with C, the saturated FAs of egg yolk decreased for MIX (p = 0.010). The polyunsaturated FAs were higher in the MIX eggs than in the C and TR eggs (p < 0.001). Although FAs were distributed in all quadrants of the principal component analysis (PCA), three main FA profiles could be identified based on the loadings of natural groupings in the PC2 versus PC1 plot. The present study shows clear evidence for the contribution of herbage to the hen diet without affecting laying performance. In addition, the FA composition of the CI and MIX vegetation contributed to the production of eggs with preferred FA attributes, such as polyunsaturated FAs and a favourable n-6 to n-3 ratio.